PERANAN PRESENTASI DESAIN DALAM PENDIDIKAN DESAIN INTERIOR - Setiawan, Andereas Pandu (Institute of Research and Community Outreach - Petra Christian University, 2003)
The development of interior design education obliges the presence of a message delivered to the design client that can be understood clearly and occurately, according to the designer's idea or to the user's demand. The design schemes that are accumulated in the student's mind are often muddled up and as a result, the message is poorly delivered to the design educator or the interior design user, although physically, the design appears to be astonishing. The same is the case when the students introduce their design work trough a poor presentation that hence causes their ideas to seem dull, their imagination not delivered and finally the design becomes raw and appears to be in the wrong direction or aim. The role of an educator and interior design education is to prepare and guide a design candidate, in this case the interior student, to develop a positive capability to be able to apply strategical step in presenting design work accurately according to the concept, imagination as well the demand of the design user. Abstract in Bahasa Indonesia : Perkembangan pendidikan desain interior menghendaki adanya penyampaian karya kepada pengguna desain (klien desain) yang dapat dipahami secara lugas, tepat, sesuai dengan gagasan perancang maupun tuntutan pengguna desain interior. Rancangan-rancangan yang ada dalam benak mahasiswa sering rancu dan akhirnya tidak tersampaikan dengan baik kepada para pendidik desain atau kepada pengguna desain interior, meskipun secara fisik tampilan karya mengagumkan. Hal ini disebabkan karena cara mahasiswa memaparkan karya lewat presentasi yang kurang tepat, sehingga gagasan-gagasan yang ada menjadi tumpul, imajinasi yang tak tersampaikan, akhirnya desain menjadi mentah dan terlihat tidak terarah dan tidak bertujuan. Peranan pendidik dan pendidikan desain interior adalah mengolah dan mengarahkan potensi positif calon desainer, dalam hal ini mahasiswa desain interior, untuk dapat melakukan langkah-langkah strategis dalam mempresentasikan karya-karyanya sesuai dengan konsep, imajinasi, dan tuntutan pengguna desain. Kata kunci : presentasi desain, pendidikan, desain interior.